1989
DOI: 10.1111/j.1570-7458.1989.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and physiological responses of rice leaffolder Cnaphalocrocis medinalis to selected wild rices

Abstract: Of four wild rices evaluated, Oryza perennis and O. punctata showed resistance to rice leaffolder, Cnaphalocrocis medinalis (Guenée), whereas O. australiensis and O. nivara were moderately resistant. C. medinalis larvae showed a strong nonpreference for settling and feeding on Oryza australiensis, O. perennis and O. nivara as compared to susceptible IR36 rice variety. Among wild rices tested, however, only O. australiensis, was more preferred for larval settling and feeding than resistant TKM6 plants. The grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
(9 reference statements)
0
12
1
Order By: Relevance
“…On the contrary, the incorporation of rice or corn leaf powder into artificial diets increased larval mortality and decreased the pupation rate. Khan et al (1989) reported that rice leaves (including susceptible and resistant varieties) had antibiosis effects on the larvae of C. medinalis, but we found that larval survival was significantly less on the diets in which leaf powder of a susceptible rice variety was incorporated than on the control without rice leaf powder. Also larval development was delayed in diets with leaf powder compared to that on the control diet.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…On the contrary, the incorporation of rice or corn leaf powder into artificial diets increased larval mortality and decreased the pupation rate. Khan et al (1989) reported that rice leaves (including susceptible and resistant varieties) had antibiosis effects on the larvae of C. medinalis, but we found that larval survival was significantly less on the diets in which leaf powder of a susceptible rice variety was incorporated than on the control without rice leaf powder. Also larval development was delayed in diets with leaf powder compared to that on the control diet.…”
Section: Discussioncontrasting
confidence: 42%
“…Also larval development was delayed in diets with leaf powder compared to that on the control diet. According to our research and Khan et al (1989), rice leaf powder or corn leaf powder is not recommended for artificial diets of C. medinalis.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae were also weighed on a Mettler balance. Leaf area scraped was measured following the method of Khan et aL (1989). The experiment was replicated 5 times.…”
Section: Methodsmentioning
confidence: 99%
“…Larval development, survival, reproduction and flight ability are significantly affected by host plant (rice) varietal differences, such as leaf morphological characteristics, cellular silicon content and wax layer thickness (Khan et al. ; Dan and Chen ; Li et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of food resources during the larval stage may cause reproductive diapause and subsequently induce emigration. Larval development, survival, reproduction and flight ability are significantly affected by host plant (rice) varietal differences, such as leaf morphological characteristics, cellular silicon content and wax layer thickness (Khan et al 1989;Dan and Chen 1990;Li et al 2013). Females that emerged from the larvae fed on rice leaf sheath showed slower ovarian development than those that fed on rice leaves (Zhang et al 1981b).…”
Section: Introductionmentioning
confidence: 99%